Universal features of particle motion in ac electric fields. (2nd October 2015) - Niemeyer, L; Seeger, M
Abstract: Mobile particles present as contaminants in high voltage gas insulated switchgear (GIS) may constitute a risk for insulation failure. The understanding of their motion in the electric field of the insulation gap is therefore essential for quality control in manufacturing, commissioning and in service monitoring. Published research on particle motion in ac electric fields has shown that this rather complex process depends on numerous parameters, many of which remain unknown under practical conditions. This renders modelling, generalization of experimental data and practical application difficult. The scope of this paper therefore is to develop a unified description of particle motion which minimizes the number of controlling parameters, enables the comparison of experimental data and allows simple interpretation relations to be derived. This is achieved by making the controlling equations dimensionless with an appropriate choice of reference values and by using simplifying assumptions for the specific conditions prevailing in GIS. The resulting generalized description of the process can then be summarized in the form of 2D patterns (dynamic maps). Approximate scaling relations are derived between specific features of these patterns and particle-related parameters. A reference case is discussed in detail. The non-linear character of the equation of motion suggests that the particle motion may be a deterministic process with chaotic features. This is confirmed by a preliminary chaos-theoretical analysis of the process.